Systematic Literature Review (SLR) Pemanfaatan Kelapa (Cocos Nucifera) dalam Pengembangan Functional Food, Nutraceutical, dan Produk Farmasi - Kusno Haryanto; Errol Rakhmad Noordam; Iin Hardiyati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Coconut (Cocos nucifera) is a tropical plant with great potential as a source of bioactives in the development of functional foods, nutraceuticals, and pharmaceutical products. This study aims to conduct a Systematic Literature Review (SLR) to synthesize scientific evidence related to its bioactive content, biological functions, and potential applications in the health and natural product-based industries. This study uses the PRISMA approach with data sources from Google Scholar, PubMed, ScienceDirect, and Scopus, and limits the literature to the period 2022–2026. From the selection process, 45 scientific articles were obtained which were analyzed thematically and narratively. The results of the study indicate that coconut contains key bioactive compounds such as Medium Chain Triglycerides (MCT), lauric acid, polyphenols, flavonoids, and phenolic compounds that have antioxidant, antimicrobial, and anti-inflammatory activities. In the context of functional foods, coconut is utilized in the form of coconut water, coconut oil, coconut milk, and processed functional food products that play a role in hydration, energy metabolism, and metabolic health management. From a nutraceutical perspective, coconuts have potential as a disease preventative agent through their immunomodulatory effects and blood glucose regulation. Furthermore, coconuts also have pharmaceutical potential as a raw material for pharmaceutical preparations, lipid-based drug delivery systems, and as a source of phytopharmaceuticals, while also supporting biotechnology and the circular economy through the utilization of their waste. However, limitations remain, such as the lack of human clinical trials and standardization of extracts, necessitating further research. In conclusion, Cocos nucifera is a strategic bioresource with significant potential for the development of functional foods, nutraceuticals, and natural-based pharmaceuticals.